Prehistoric sound tube: A preliminary international panorama - Araujo, Giusepe Augusto; Blanco, Pablo Sotuyo (Revista do Museu de Arqueologia e Etnologia, 2023)
This text presents a broad international overview of archaeomusicological research on prehistoric sound tube-type aerophones (including whistles and flutes), including an expressive set of items located outside Brazil, on four continents: Africa, America, Asia and Europe. The theoretical foundation that conceptually underpinned the research that gave rise to this article, as well as the methodology used, cover fields of knowledge such as Information Science (Library Science, Archival Science, Museology), Archeology and Musicology (Acoustics and Organology), with its interdisciplinary articulated use. Since there are no previous studies in Brazil on this subject in such an incipient area of ​​knowledge (as is archaeomusicology), either due to lack of knowledge of musicological tools, or due to the lack of criticism in archaeological analysis, it was necessary to review the available literature, whose results we present.